A Synergistic STEM-Creativity Model to Enhance Cognitive Innovation and Higher-Order Thinking Skills (HOTS) in Mathematics Learning - Hendi Hidayah; Abdillah; Sirajuddin; Syaharuddin; Wasim Raza; Sunday Emmanuel Fadugba (Jurnal Pendidikan Indonesia, 2026)
Students’ low levels of cognitive innovation and higher-order thinking skills (HOTS) in mathematics learning remain a major problem caused by teacher-centered instruction and a lack of contextual problem-solving activities. This study aims to analyze and test the effectiveness of the Synergistic STEM–Creativity Learning Model in improving students’ cognitive innovation and HOTS in mathematics learning. This study employs a quantitative approach with a quasi-experimental pretest–posttest control group design. The research participants consisted of 68 junior high school students divided into an experimental class and a control class. Data collection was conducted through HOTS essay tests and Likert scale questionnaires to measure students’ cognitive innovation abilities. The data were analyzed using assumption tests, hypothesis tests, and N-Gain to evaluate the improvement in abilities and differences in learning outcomes between groups. The results of the study indicate that students in the experimental class demonstrated a greater improvement in cognitive innovation and higher-order thinking skills (HOTS) compared to students in the control class. The Synergistic STEM–Creativity Learning Model is capable of encouraging students to think more creatively, analytically, and reflectively through contextual and collaborative learning activities. These findings suggest that this learning model is effective in developing students’ higher-order thinking skills and cognitive innovation in mathematics education.